2020
DOI: 10.3389/fphys.2020.00735
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Role of Calcium/Calmodulin-Dependent Protein Kinase in Cardiorenal Syndrome

Abstract: Calcium/calmodulin-dependent protein kinases (CaMKs) are key regulators of calcium signaling in health and disease. CaMKII is the most abundant isoform in the heart; although classically described as a regulator of excitation-contraction coupling, recent studies show that it can also mediate inflammation in cardiovascular diseases (CVDs). Among CVDs, cardiorenal syndrome (CRS) represents a pressing issue to be addressed, considering the growing incidence of kidney diseases worldwide. In this review, we aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 122 publications
(161 reference statements)
0
33
0
Order By: Relevance
“…The intracellular Ca 2+ concentration is directly modulated by influx (from the extracellular space or endoplasmic reticulum), mediated via several types of Ca 2+ channels. The intracellular Ca 2+ interacts with and activate a variety of calcium-binding effector proteins (e.g., Calmodulin (CaM)) and Ca 2+ -dependent protein kinase (CDPK) [ 67 , 68 , 69 ]. Collectively, CaM and CDPK activate several sets of other CaM kinases (CaMKs); once CaMKs are activated, they can modulate several other intermediate signaling molecules ( Figure 2 D) and transcription factors to regulate cell fate and differentiation [ 67 , 68 , 69 , 70 ].…”
Section: Overview Of Major Signaling Pathways and Targets Involved In Organizer-induced Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular Ca 2+ concentration is directly modulated by influx (from the extracellular space or endoplasmic reticulum), mediated via several types of Ca 2+ channels. The intracellular Ca 2+ interacts with and activate a variety of calcium-binding effector proteins (e.g., Calmodulin (CaM)) and Ca 2+ -dependent protein kinase (CDPK) [ 67 , 68 , 69 ]. Collectively, CaM and CDPK activate several sets of other CaM kinases (CaMKs); once CaMKs are activated, they can modulate several other intermediate signaling molecules ( Figure 2 D) and transcription factors to regulate cell fate and differentiation [ 67 , 68 , 69 , 70 ].…”
Section: Overview Of Major Signaling Pathways and Targets Involved In Organizer-induced Embryonic Developmentmentioning
confidence: 99%
“…The intracellular Ca 2+ interacts with and activate a variety of calcium-binding effector proteins (e.g., Calmodulin (CaM)) and Ca 2+ -dependent protein kinase (CDPK) [ 67 , 68 , 69 ]. Collectively, CaM and CDPK activate several sets of other CaM kinases (CaMKs); once CaMKs are activated, they can modulate several other intermediate signaling molecules ( Figure 2 D) and transcription factors to regulate cell fate and differentiation [ 67 , 68 , 69 , 70 ]. In recent years, many important reports have demonstrated that Ca 2+ is essential for involuting/migrating mesodermal cells [ 71 , 72 ].…”
Section: Overview Of Major Signaling Pathways and Targets Involved In Organizer-induced Embryonic Developmentmentioning
confidence: 99%
“…Genetic variants in eNOS have been associated with low nitric oxide concentrations and vascular density [32][33][34][35]. Among these genes, the calcium/calmodulin kinase family proteins represent a group of genes particularly associated with CVDs [24,36,37]. Among them, CAMK2 is the most studied in the contest of the physiology of the heart [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, the calcium/calmodulin kinase family proteins represent a group of genes particularly associated with CVDs [ 24 , 36 , 37 ]. Among them, CAMK2 is the most studied in the contest of the physiology of the heart [ 38–40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium (Ca 2+ ) is an intracellular universal second messenger that regulates a variety of cellular processes. Many biological processes, including gene transcription, cell cycle, migration, and apoptosis, are affected by changes in intracellular Ca 2+ signaling [ 1 , 2 ]. Disruption of normal Ca 2+ signaling can cause tumorigenic phenotypes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%